Equity market integration of China and Southeast Asian countries: further evidence from MGARCH-ADCC and wavelet coherence analysis - Ngo Thai Hung (Quantitative Finance and Economics, 2019)
This paper investigates the short-term and long-term dynamics between China and four Southeast Asian countries (Vietnam, Thailand, Singapore and Malaysia) during period 2008–2018. Our empirical research is based on the Generalized Autoregression Conditional Heteroscedasticity-Asymmetric Dynamic Conditional Covariance (MGARCH-ADCC) model and the wavelet coherence technique which allow us to estimate the time-varying correlation and the co-movement in both time-frequency spaces of stock markets of China and its neighboring countries. The results of the study reveal that stock markets of China and its trading partners are relatively integrated after the global financial crisis of 2008, frequency changes in the pattern of the co-movements and a positive linkage throughout the sample period. Specifically, the conditional correlation of stock returns between China and Singapore is more significantly influenced by negative innovations than by positive shocks to return. Furthermore, the study provides evidence of significant coherence between both the variables for almost the entire studied period in long scale. Therefore, these findings are positive signs for the Chinese and international investors to diversify their portfolio among the stock markets of China and its trading partners.